Highly Conductive Poly(3,4-ethylenedioxythiophene) Polystyrene Sulfonate Polymer Coated Cathode for the Microbial Electrosynthesis of Acetate From Carbon Dioxide - Aryal, Nabin; Tremblay, Pier-Luc; Xu, Mengying; Daugaard, Anders E.; Zhang, Tian (Frontiers in Energy Research, 2018)
Microbial electrosynthesis (MES) is a bioelectrochemical technology developed for the conversion of carbon dioxide and electric energy into multicarbon chemicals of interest. As with other biotechnologies, achieving high production rate is a prerequisite for scaling up. In this study, we report the development of a novel cathode for MES, which was fabricated by coating carbon cloth with conductive poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) polymer. Sporomusa ovata-driven MES reactors equipped with PEDOT:PSS-carbon cloth cathodes produced 252.5 ± 23.6 mmol d−1 acetate per m2 of electrode over a period of 14 days, which was 9.3 fold higher than the production rate observed with uncoated carbon cloth cathodes. Concomitantly, current density was increased to −3.2 ± 0.8 A m−2, which was 10.7-fold higher than the untreated cathode. The coulombic efficiency with the PEDOT: PSS-carbon cloth cathodes was 78.6 ± 5.6%. Confocal laser scanning microscopy and scanning electron microscopy showed denser bacterial population on the PEDOT:PSS-carbon cloth cathodes. This suggested that PEDOT:PSS is more suitable for colonization by S. ovata during the bioelectrochemical process. The results demonstrated that PEDOT: PSS is a promising cathode material for MES.